Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae) - Liu, Xiaoyan; Yang, Ding (Zootaxa, 2016)
A review of the species of the genus Lasiosina Becker from China is provided. The following two species are described as new to science: L. nigrolineata sp. nov. and L. recurvata sp. nov. A key to all species of Lasiosina from China is given.